(untitled) (Journal of Surgical Sciences, 2020)
Background: Acute appendicitis is one of the important causes of emergency surgeries. Diagnosis of acute appendicitis remains to be challenging with up to 30% negative exploration rates. In addition to careful clinical history and physical examination, we still need easily applicable, cheap and effective biomarker. Complete blood count is the primary investigation for any inflammatory condition. Total WBC count and neutrophil percentage are widely used biomarkers to diagnose acute appendicitis. Mean platelet volume (MPV) is an emerging biomarker that has been considered to be affected by inflammatory burden. MPV value is also estimated during complete blood count. This study may help to reveal the change of MPV in acute appendicitis. Study design: This was a prospective observational type of study. Study setting and period: The study was carried out in the Surgery In-patient Department of Dhaka Medical College Hospital, Dhaka from 15-11-2013 till 15-04-2014. Materials: A total of 150 patients of both sex aged 15-65 years who got admitted in the surgery department for acute appendicitis were selected. Pediatric patients (aged less than 14years), patients with co morbid illness like ischemic heart disease, inflammatory bowel disease, general peritonitis and the patients having lack of necessary investigations were excluded from the study. Methods: The variables like total WBC count, neutrophil percentage, platelet count and mean platelet volume (MPV) of all 150 selected patients were noted after admission by doing complete blood count and compared with normal value. The appendix samples obtained after surgery were sent for histopathological confirmation and reports were collected. Results: A total of 150 patients with the mean age of 25.72 (ranging 15-65) years were studied. Among them 93(62%) were male and 57(38%) were female. Mean MPV value was 11.7 ± 0.183 fL (p value 0.02). 122 patients have increased MPV value (81.33%). Among them 113 were eventually diagnosed as acute appendicitis. Negative exploration rate was 14%.Negative exploration was less among MPV raised patients (7.38%). Whereas negative exploration was more among normal MPV patients (21.42%).Total WBC count and neutriphil percentage are important biomarkers to diagnose acute appendicitis which is accepted. However this study revealed MPV value is an important biomarker in acute appendicitis also which is statistically significant and can reduce negative exploration. Conclusion: In this study mean platelet volume increases in acute appendicitis. MPV can be used as a biomarker in diagnosis of acute appendicitis. Journal of Surgical Sciences (2018) Vol. 22 (2) : 83-88